Diversidade genética entre cultivares de Mandioca da Região Oeste do Paraná - Egewarth, Jonas Francisco (2014)
The present study was conducted to evaluate the genetic diversity through quantitative and qualitative morphological characteristics in cassava cultivars used by farmers in western region of Paraná State. For both 24 cassava genotypes were collected, and they are subjected to experimental testing conducted in the municipality of Marechal Candido Rondon in the agricultural year 2012/2013. The field trial was implemented following the randomized complete block design with three replications in area situated 24 33 ' south latitude and 54 31' west longitude, and altitude of 420 m. The genetic diversity was performed with the qualitative characters (21 descriptors) and then quantitative (9 descriptors). After tabulating the data was performed obtaining the Euclidean distance matrix for the qualitative and quantitative characteristics for the Mahalanobis and then made up the clustering structure by Tocher methods, UPGMA and nearest neighbor for each array away, with the data quality characteristics also employed the method of Tocher optimization. For qualitative characteristics was found that genotypes Fécula Branca, Cascuda 6, Baianinha 2 and 3 were different from other genotypes of their varieties, existing variability among these varieties or specimens, these examples do not correspond to their respective manifolds. Genotypes Vermelha Uma Rama 1 and 2 were split in all methods, demonstrating that they have inter-variability, evaluated for quality characteristics, not being from the same genetic material. With the data of quantitative traits was found that the genotype of Fécula Branca 3 was different from the other genotypes of the same nomenclature. The other genotypes fécula branca presented in the same group, along with the genotypes of husky. Genotypes Vermelha Uma Rama 1 and 2 were split in all methods, demonstrating that they possess variability among themselves, the set of traits. The Baianinha 1 genotype was different from Baianinha genotypes 2 and 3, showing the existence of variation between them for traits